Fucoxanthin promotes the chain lengthening reaction of polyunsaturated fatty acids in vivo by enhancing FADS2 enzyme activity - Xiaoyue Li; Tianxin Yang; Yingcai Zhao; Chengcheng Wang; Changhu Xue; Teruyoshi Yanagita; Yuming Wang; Tiantian Zhang (Food Science and Human Wellness)
Alpha-linolenic acid (ALA) is capable of synthesizing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in vivo, but the conversion rate is hard to meet the body's need for rapid DHA supplementation. Studies have shown that fucoxanthin can increase DHA content in the liver of mice, but the mechanism is not clear. Moreover, the effect of fucoxanthin and its metabolite fucoxanthinol on the chain lengthening reaction of n-6 polyunsaturated fatty acids (PUFAs) is little studied. In this study, the effects of fucoxanthin and fucoxanthinol on the chain elongation of n-3 and n-6 series PUFAs were investigated in mice. Results showed that fucoxanthin and fucoxanthinol significantly increased the conversion of n-3 series ALA to DHA and n-6 series linolenic acid (LA) to arachidonic acid (AA) in the serum, liver, small intestine, and heart of mice. In addition, fucoxanthin accelerated the rate of DHA supplementation by ALA in the brain. Further mechanistic studies revealed that the role of fucoxanthin in promoting PUFAs conversion was not regulated at transcriptional level, but by increasing the activity of fatty acid desaturase 2 (FADS2), a key enzyme of chain elongation reaction of n-3 and n-6 PUFAs. This study fundamentally provided theoretical bases for a new strategy of dietary supplementation of n-3 and n-6 PUFAs.